The rise of the Fatimids, 280-296 A.H. 893-909 C.E. - Wan Ibrahim, Wan Asma; Islam, Arshad (IIUM Press, International Islamic University Malaysia, 2017)
This research examines local factors that helped the rise of the Fatimids in North Africa in 296 A.H./909 C.E. The socio-religious, political and economic conditions of the region provided fertile ground for the Isma'ili dāʿī, Abū ʿAbd Allāh al-Shīʿī to implement his da’wa strategies. The prevalence of Islam in the region and its sectarian groups facilitated the acceptance of the Isma'ili doctrine among the populace. The poor control of the ʿAbbasids over the region and the emergence of local independent states such as the Midrarids, Rustamids and Idrisids convinced the Fatimids to select the North Africa as their stronghold, with the promise of establishing their state based on the rich sub-Saharan trade. Thus, when the internal turbulence faced by the Isma'ilis in Salamiyya forced the Imām to flee, he naturally headed to North Africa due to the encouraging progress of his dāʿī there. The Aghlabids’ meanwhile had successfully alienated all potential sources of support and the general public, antagonising the religious institutions and Arab militias and levying large cash taxes on the population in the late third/ninth century, making the Fatimids appear to be rescuers to many inhabitants. Al-Shīʿī approached a local proto-Shīʿa community, the Kutama, who later became the stalwart of his military forces, ingratiating himself with them as a religious teacher and then leader. Having consolidated his control over this tribe, al-Shīʿī went on to forge a multi-tribal confederation that swept across North Africa and destroyed the Aghlabid mercenary forces. Furthermore, the last Aghlabid amīr, Ziyādat Allāh III, failed to secure his own people’s confidence due to his corrupt administrative system and dissolute court. Al-Shīʿī also successfully conquered the important trade cities such as Qayrawān, Tahart and Sijilmasa, permanently securing his supplies and making North Africa the engine of the Fatimid aspiration to statehood.